Ventilator-associated pneumonia in patients using HME filters and heated humidifiers - OĞUZ, SIDIKA (SPRINGER LONDON LTD, 2013)
Ventilator-associated pneumonia (VAP) is a clinical form of hospital-associated pneumonia, which may develop within 48 h in patients on mechanical ventilation who had no pre-existing pneumonia at the time of intubation. The objective of this study was to compare the incidence of VAP among patients who started receiving treatment with heat and moisture exchanger (HME) filters and heated humidifiers (HHs) for mechanical ventilation. Patients who were on the first day of intubation, did not have pre-intubation pneumonia, presented to the healthcare centre with no infections at the time of presentation, were not on antibiotic treatment for pulmonary infections and did not have evidence of infiltration with chest radiography were included in the study. Data were evaluated using Fischer's exact, Mann-Whitney's U and t tests. The patients in the HME filter and HHs groups had a mean age of 47.9 +/- A 2.2 and 44.5 +/- A 2.1 years, respectively. Infiltration on chest radiography was identified on day 6.33 for the patients in the HME filter group and on day 5.8 in the HHs group. Patients using HME filters and HHs did not differ significantly with regard to the day of mechanical ventilation and number of days hospitalized (p > 0.5). Comparison of the two groups with regard to presence of fever during the first 24 h, however, demonstrated higher than expected values for the patients using HHs, with a significant difference (p = 0.001). There were no significant differences between the groups on HME filters and heated humidifiers in terms of infection development; although pulmonary radiography showed delayed average days to infiltration development for subjects using HME filters.
Keywords: HME filter; HHs; VAP; Nursing; MOISTURE EXCHANGERS